2008
DOI: 10.1093/jn/138.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Physical Activity Patterns in French Children Are Related to Overweight and Socioeconomic Status

Abstract: Sedentary behavior (SED) has already been identified as a risk factor of childhood overweight (OW) but less is known about the dietary patterns related to adiposity. Our objective was to investigate if lifestyle patterns combining overall diet and physical activity were associated with childhood OW and if they were involved in the reverse association between socioeconomic status (SES) and OW. Dietary intake was assessed using a 7-d food record in 748 French children aged 3-11 y from the 1998-1999 cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
145
2
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(176 citation statements)
references
References 28 publications
20
145
2
9
Order By: Relevance
“…Similarly, the traditional Lebanese pattern, which builds on higher intakes of breads and cereals, dairy products, fruits and vegetables and traditional Lebanese mixed dishes, is similar to the Traditional pattern reported in previous studies conducted amongst adolescents and adults in the country [38][39][40]. In agreement with our findings, Lioret et al and Manios et al have also identified two dietary patterns amongst French and Greek preschoolers, respectively, with the identified patterns being similar to those derived in the present study, even though the specific foods belonging to each pattern may vary in their respective level of contribution [18,19]. Other studies have, however, characterized more than two patterns amongst preschoolers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, the traditional Lebanese pattern, which builds on higher intakes of breads and cereals, dairy products, fruits and vegetables and traditional Lebanese mixed dishes, is similar to the Traditional pattern reported in previous studies conducted amongst adolescents and adults in the country [38][39][40]. In agreement with our findings, Lioret et al and Manios et al have also identified two dietary patterns amongst French and Greek preschoolers, respectively, with the identified patterns being similar to those derived in the present study, even though the specific foods belonging to each pattern may vary in their respective level of contribution [18,19]. Other studies have, however, characterized more than two patterns amongst preschoolers.…”
Section: Discussionsupporting
confidence: 93%
“…In this context, dietary pattern analysis was proposed as a holistic approach that investigates the joint effects of multiple dietary components on obesity risk [16,17]. Few studies have examined dietary patterns amongst preschoolers and their association with the risk of overweight or obesity [18][19][20][21][22]. A dietary pattern rich in French fries and sweetened beverages and low in dairy products and water was found to be associated with increased risk of overweight and obesity amongst 3-6-year-old French children [18].…”
Section: Introductionmentioning
confidence: 99%
“…50 Our study is also one of few among adults that have analyzed the co-occurrence of physical activity and sedentary behaviors 22 compared with a number of studies conducted in adolescents. [23][24][25][26]51,52 Despite variations in specific types of physical activity performed by men and Physical activity clusters and overweight H Charreire et al women, a cluster named 'multiple activity/low TV' was observed in both sexes. However the cluster including 'walking and gardening only' (cluster 1) was associated with a low level of sedentary occupation in men (low TV) and a high level of sedentary occupation in women (high TV).…”
Section: Discussionmentioning
confidence: 98%
“…Corroborando esses achados, estudos europeus e americanos apontam que o consumo do açúcar de adição vem crescendo, variando de 14 a 29%, e sendo inversamente associado ao consumo de gorduras, vitaminas e minerais 28 . Padrão alimentar com composição similar foi encontrado em estudos com adolescentes mexicanas 29 , crianças coreanas 25 e francesas 30 .…”
Section: I S C U S S ã Ounclassified